Description and quantification of pteropod shell dissolution: a sensitive bioindicator of ocean acidification - Nina Bednaršek; Geraint A Tarling; Dorothee CE Bakker; Sophie Fielding; Anne Cohen; Alan Kuzirian; Dan McCorkle; Bertrand Lézé; Roberto Montagna (Global Change Biology, 2012)
Anthropogenic ocean acidification is likely to have negative effects on marine calcifying organisms, such as shelled pteropods, by promoting dissolution of aragonite shells. Study of shell dissolution requires an accurate and sensitive method for assessing shell damage. Shell dissolution was induced through incubations in CO 2 ‐enriched seawater for 4 and 14 days. We describe a procedure that allows the level of dissolution to be assessed and classified into three main types: Type I with partial dissolution of the prismatic layer; Type II with exposure of underlying crossed‐lamellar layer, and Type III , where crossed‐lamellar layer shows signs of dissolution. Levels of dissolution showed a good correspondence to the incubation conditions, with the most severe damage found in specimens held for 14 days in undersaturated condition (Ω ~ 0.8). This methodology enables the response of small pelagic calcifiers to acidified conditions to be detected at an early stage, thus making pteropods a valuable bioindicator of future ocean acidification.

The anatomy of population change in a black grouse population 1992–2008 - Matthew Geary; Alan H. Fielding; Stuart J. Marsden (Oecologia, 2012)

Analysing Extinction Risk in Parrots using Decision Trees - Martin J. Jones; Alan Fielding; Matthew Sullivan (Biodiversity and Conservation, 2006)

A Comparison of Predictive Methods in Extinction Risk Studies: Contrasts and Decision Trees - Matthew S. Sullivan; Martin J. Jones; David C. Lee; Stuart J. Marsden; Alan H. Fielding; Emily V. Young (Biodiversity and Conservation, 2006)

How Well Will Brazil's System of Atlantic Forest Reserves Maintain Viable Bird Populations? - Stuart J. Marsden; Mark Whiffin; Mauro Galetti; Alan H. Fielding (Biodiversity and Conservation, 2005)

Habitat associations of parrots on the Wallacean islands of Buru, Seram and Sumba - Stuart Marsden; Alan Fielding (Journal of Biogeography, 1999)
Summary Aim To investigate patterns of habitat use in nineteen populations of parrots on three Wallacean islands, and examine the degree to which habitats used by a species can be predicted across islands. Location The Wallacean islands on Buru, Seram and Sumba. Methods A logistic regression method was used to relate the presence/absence of parrot species at census plots to vegetation axes derived from ‘gross’ habitat parameters such as altitude, tree sizes, and percentages of vegetation coverage at different strata. Receiver Operating Characteristic Plots were then used to test predictions of habitat use by conspecific populations on the nearby and distant islands, and by different parrot species on the same island. Results Parrots on Buru and nearby Seram tended to be associated with open‐canopied lowland forests, while on the distant and low‐lying island of Sumba, the preference was for closed‐canopy forests at higher altitudes. There were usually close affinities in habitat usage by conspecific populations on the two nearby islands. One exception was where the species occurred on the two islands as separate subspecies. Habitat preferences on Sumba, however, were so distinct that paradigms developed for Buru and Seram failed to predict distributions on this distant island. Main conclusions For populations on more distant islands, it will usually be better to predict habitat use by considering the habitat used by other parrot species occurring on that island, than a conspecific population from another region. Conservation research programmes which concentrate parrot study on just one or two islands in every region of Wallacea may be more successful than those which ‘run through’ several islands in a group, but which miss out whole regions.